Analisis Penerapan Nilai-Nilai Pancasila Sebagai Sistem Filsafat dalam Lingkungan Kampus - Friska Melina Panggabean; Nadya Anandra; Rima Nurdiani Harahap; Sri Bina Br Sembiring; Yosafat Yeduhardy Gultom (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to investigate how Pancasila values are applied as a philosophical framework in university campuses, specifically at Universitas Negeri Medan (UNIMED). This study examined students in UNIMED's English education program's awareness and application of Pancasila values through a hybrid method comprising surveys and literature reviews. The results demonstrate that the majority of respondents actively incorporate Pancasila basic values into their everyday activities on campus and have a clear knowledge of their significance. However, completely embracing the values is not without its difficulties. It is advised to increase knowledge, application, and reflection on the fundamental, practical, and instrumental elements of Pancasila in order to enhance the integration of Pancasila ideals on campus. Programs that encourage the comprehension and application of Pancasila ideals as well as support from educational establishments to raise awareness of these values as a moral and social cornerstone on campus can accomplish this.